PENGARUH PEMANFAATAN CREAM CREAMBATH LIDAH BUAYA TERHADAP PERAWATAN RAMBUT - Mukti, Suci; Rostamailis, Rostamailis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aims to analyze the effect of the use of aloe vera cream bath cream to hair treatment. Indicators in this study were observed from changes in the level of hair loss. This research was pre-experimental design with a one-group pretest-posttest. The object of this study is to experiencing dry hair loss, while the sample in this study were women who have the same age range which ranges between 19 to 25 years, experiencing hair loss. Data collected from this research is primary data obtained directly from the sample by filling out the assessment form has been provided. The research data were analyzed using normality test, homogeneity, and t-test. Based on the results of the data found that the magnitude of the numbers normality test of significance Î± = 0.05 it can be seen that 0.692> 0.05. This means that the data is normally distributed. Results of the homogeneity test F-4 and F-table count obtained at 6.39. Followed by t-test with the results obtained by -6.325 t and p value of 0.003. This means that there is a significant effect on hair treatment with the use of aloe vera cream of cream bath.Keywords: The use of aloe vera cream of cream bath, hair loss treatment.